The Association Between Haloperidol and Clozapine and The Risk of Hyperglycaemia in Patients with Schizophrenia - Martanty Aditya; Godeliva Adriani Hendra; Rina Setyowati (Jurnal Farmasi Ma Chung: Sains, Teknologi, dan Klinis Komunitas, 2026)
First- and second-generation antipsychotics such as haloperidol and clozapine are treatment options for schizophrenia; however, both have the potential for metabolic side effects, including hyperglycemia. This study aimed to analyse the association between using haloperidol or clozapine, either alone or together, and the occurrence of hyperglycemia in patients with schizophrenia. The research used an observational design with a cross-sectional study and retrospective data from 154 medical records of schizophrenia patients. The study was conducted at Dr. Radjiman Wediodiningrat Psychiatric Hospital outpatient clinic, Lawang, from January to March 2025. Data were analysed using the chi-square test and odds ratio with RStudio 2024. The results showed that most patients received clozapine alone or with other medications (70.78%). A significant association was found between clozapine use and male sex (p = 0.014) as well as the 17–40 age group (p = 0.001). Haloperidol use was linked to an increased risk of elevated creatinine levels (p = 0.026). However, there was no significant link between the type of therapy and the risk of hyperglycemia (OR = 1.243; 95% CI: 0.097–66.819). Levels of SGOT (p = 0.913), SGPT (p = 0.258), and urea (p = 1.000) stayed within normal limits in both treatment groups. In summary, clozapine may carry a slightly higher but statistically insignificant risk of causing hyperglycemia. Overall, treatment with haloperidol or clozapine appears safe concerning liver and kidney function, as indicated by normal SGOT, SGPT, and urea levels.